Liraglutide inhibits the development of colorectal cancer by regulating TGF-β/Smad3 signaling pathway and affecting epithelial-mesenchymal transition - Xinjian Li; Minghu Fan; Rong Huang; Keqiang Wang; Hunan Huang (Discover Oncology)
Abstract Background Liraglutide, a glucagon-like peptide-1 receptor agonist commonly used in diabetes management, has shown potential anti-cancer effects across various malignancies. However, its role and underlying mechanisms in colorectal cancer (CRC) remain unclear. Method We investigated the effects of Liraglutide on human normal colon epithelial (NCM-460) and colorectal cancer (CRC) cells (LoVo and HCT116) using varying concentrations. Cell viability, proliferation, apoptosis, cell cycle progression, migration, invasion, and the expression of TGF-β/Smad3 and EMT-related markers were assessed. Additionally, we explored the effects of TGF-β agonists on the TGF-β/Smad3 signaling pathway. Tumor growth was evaluated in a nude mouse model. Result Liraglutide reduced CRC cell proliferation in a dose-dependent manner, with the high-concentration treatment (Liraglutide-H) showing the most potent effect (p < 0.01 for Liraglutide-L, p < 0.0001 for Liraglutide-H). High-dose Liraglutide (Liraglutide-H) promoted apoptosis and induced G1-S phase arrest (p < 0.05). Migration and invasion of CRC cells were significantly reduced in both treatment groups (p < 0.05), with Liraglutide-H showing the strongest inhibitory effect. Liraglutide also modulated the TGF-β/Smad3 pathway: it decreased TGF-β, p-Smad3/Smad3 and N-cadherin levels while increasing E-cadherin levels (p < 0.05). These effects were reversed by the addition of a TGF-β agonist (p < 0.05). Conclusion Liraglutide inhibits CRC progression by modulating the TGF-β/Smad3 signaling pathway, which affects EMT, cell migration, and invasion. These findings suggest a potential therapeutic role for Liraglutide in CRC treatment.